2011
DOI: 10.3402/fnr.v55i0.5961
|View full text |Cite
|
Sign up to set email alerts
|

Increased postprandial glycaemia, insulinemia, and lipidemia after 10 weeks’ sucrose-rich diet compared to an artificially sweetened diet: a randomised controlled trial

Abstract: BackgroundThe importance of exchanging sucrose for artificial sweeteners on risk factors for developing diabetes and cardiovascular diseases is not yet clear.ObjectiveTo investigate the effects of a diet high in sucrose versus a diet high in artificial sweeteners on fasting and postprandial metabolic profiles after 10 weeks.DesignHealthy overweight subjects were randomised to consume drinks and foods sweetened with either sucrose (∼2 g/kg body weight) (n = 12) or artificial sweeteners (n = 11) as supplements t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 36 publications
1
53
0
1
Order By: Relevance
“…Recently, Stanhope and colleagues showed that c onsuming beverages containing 10%, 17.5%, or 25% of energy requirements from HFCS produced significant linear dose-response increases in postprandial triglycerides, fasting LDL cholesterol and 24-hour mean uric acid concentrations in a 2-week parallel-arm, nonrandomized double blinded intervention study (11). Raben et al found that a sucrose-rich diet consumed for 10 weeks resulted in significant elevations of postprandial glycemia, insulinemia, and lipidemia compared to a diet rich in artificial sweeteners in overweight healthy subjects (33). A randomized crossover trial among normal weight healthy men found that after 3 weeks, SSBs consumed in small to moderate quantities (600 mL SSB/day containing 40–80 g of sugar) significantly impaired glucose and lipid metabolism and promoted inflammation (34).…”
Section: Rcts Of Fructose Ssbs and Cardiovascular Risk Markersmentioning
confidence: 99%
“…Recently, Stanhope and colleagues showed that c onsuming beverages containing 10%, 17.5%, or 25% of energy requirements from HFCS produced significant linear dose-response increases in postprandial triglycerides, fasting LDL cholesterol and 24-hour mean uric acid concentrations in a 2-week parallel-arm, nonrandomized double blinded intervention study (11). Raben et al found that a sucrose-rich diet consumed for 10 weeks resulted in significant elevations of postprandial glycemia, insulinemia, and lipidemia compared to a diet rich in artificial sweeteners in overweight healthy subjects (33). A randomized crossover trial among normal weight healthy men found that after 3 weeks, SSBs consumed in small to moderate quantities (600 mL SSB/day containing 40–80 g of sugar) significantly impaired glucose and lipid metabolism and promoted inflammation (34).…”
Section: Rcts Of Fructose Ssbs and Cardiovascular Risk Markersmentioning
confidence: 99%
“…Previous research has identified that a diet high in fructose induces hepatic DNL, causing an increase in plasma TG and VLDL concentrations (1, 29, 33). In addition, although not studied in this particular study, physical inactivity may reduce LPL activity resulting in reduced rates of fatty acid utilization and oxidation in peripheral tissues (35).…”
Section: Discussionmentioning
confidence: 99%
“…Ford et al [28] sécrétion. Chez l'homme en surcharge pondérale mais en bonne santé, Raben et al [30] ont montré qu'une diète enrichie en édulcorants intenses pendant 10 semaines ne modifie pas les paramètres biologiques post prandiaux qu'il s'agisse de la glycémie, de l'insulinémie, de la concentration en leptine ou du GLP1. Ils notent également qu'aucun paramètre lipidique n'est modifié.…”
Section: Mots Clés éDulcorants · Aspartame · Obésité · Poidsunclassified